2022
DOI: 10.1101/2022.06.23.22276492
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biological Brain Age Prediction Using Machine Learning on Structural Neuroimaging Data: Multi-Cohort Validation Against Biomarkers of Alzheimer’s Disease and Neurodegeneration stratified by sex

Abstract: Brain-age can be inferred from structural neuroimaging and compared to chronological age (brain-age delta) as a marker of biological brain aging. Accelerated aging has been found in neurodegenerative disorders like Alzheimer’s disease (AD), but its validation against markers of neurodegeneration and AD is lacking. Here, imaging-derived measures from the UK Biobank dataset (N=22,661) were used to predict brain-age in 2,314 cognitively unimpaired (CU) individuals at higher risk of AD and mild cognitive impaired … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 86 publications
1
8
0
Order By: Relevance
“…We found that predicted brain ages generated by a densely connected neural network using 3 distinct sets of neuroimaging features (FW-corrected dMRI, T1-weighted MRI, combined FW+T1) all showed high correlation with actual age in baseline CU participants, which confirms findings from previous literature that have accurately predicted chronological age of healthy adults using neuroimaging-derived measures with machine learning approaches including deep learning 11,12,17,2629 . Importantly, the top-contributing neuroimaging features identified for each model ( Figure 2 ) provide biological interpretability as they include brain regions that have been associated with both normal aging and AD neuropathology.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We found that predicted brain ages generated by a densely connected neural network using 3 distinct sets of neuroimaging features (FW-corrected dMRI, T1-weighted MRI, combined FW+T1) all showed high correlation with actual age in baseline CU participants, which confirms findings from previous literature that have accurately predicted chronological age of healthy adults using neuroimaging-derived measures with machine learning approaches including deep learning 11,12,17,2629 . Importantly, the top-contributing neuroimaging features identified for each model ( Figure 2 ) provide biological interpretability as they include brain regions that have been associated with both normal aging and AD neuropathology.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, individuals with a higher predicted brain age at baseline were more likely to convert from MCI to AD 42 or develop dementia later in life 18 . Studies generating predicted age difference from structural MRI scans of healthy controls have also found correlations with performance on traditional screening tools for AD (e.g., Mini-Mental State Examination, Clinical Dementia Ratio), anatomical measurements such as cortical thickness and hippocampal volume 43 , AD neuropathology such as β-amyloid positivity 16,26 , and AD risk factors such as APOE-4 carrier status 16,26 . We also found that all predicted brain ages were robustly associated with cross-sectional and longitudinal cognitive function including baseline memory and executive function scores and longitudinal memory and executive function slopes.…”
Section: Predicted Age Is a More Sensitive Measure Than Actual Age An...mentioning
confidence: 99%
“…The precise prediction of both chronological and biological age in PD constitutes a clinically significant task. Recent machine learning studies have leveraged extensive datasets, such as the UK Biobank brain imaging data, to construct brain-age models and investigate various aging-related hypotheses [23,24]. One approach involves calculating the brain-age delta by subtracting chronological age from the estimated brain age [25].…”
Section: Related Workmentioning
confidence: 99%
“…A brain age estimation higher than that of healthy agematched peers has already been linked to AD [13][14][15][16], Parkinson's disease [17], Schizophrenia [16,[18][19][20], Multiple Sclerosis [21][22][23], as well as to life expectancy [24]. Various brain age models exist [25], but tend to be rather complex in their interpretation.…”
Section: Introductionmentioning
confidence: 99%